Technical progress and the pattern of specialization in world trade in manufactures, 1965 to 1987 - Matthias Lücke (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1992)
It has been hypothesized that technical progress will erode the competitiveness of the manufactured exports of developing countries. The paper tests two assumptions underlying this hypothesis. First, limited technological competence might prevent developing countries from competing effectively in industries with rapid technological change. Secondly, increases in labour productivity might reduce the importance of low labour costs as a determinant of competitiveness. This paper presents a crosscountry, cross-industry econometric analysis of the determinants of specialization in trade in manufactures, covering 3 7 industrialized and developing countries. Neither hypothesized relationship is supported by the data.
Keywords: O33; F14; 330; Internationale Arbeitsteilung; Internationaler Wettbewerb; Technischer Fortschritt; Industriestaaten; Entwicklungsländer